2015
DOI: 10.1590/s0102-865020150080000006
|View full text |Cite
|
Sign up to set email alerts
|

Intra and postoperative evaluations of microcirculation and micro-rheological parameters in a rat model of musculocutaneous flap ischemia-reperfusion

Abstract: PURPOSE:To examine how the ischemia-reperfusion injury of latissimus dorsi-cutaneous maximus (LDCM) musculocutaneous flap affects the microcirculatory (flap's skin surface) and hemorheological parameters, and whether an intraoperative deterioration would predictively suggest flap failure in the postoperative period. METHODS:Ten healthy male rats were subjected to the study. In Group I the left flap was sutured back after 2-hour, while the contralateral side was right after its elevation. In Group II the same t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Klarik et al examined the hemorheological (red blood cell deformability and aggregation) and microcirculatory parameters (laser Doppler fluxmetry) after two-hour ischemia in latissimus dorsicutaneus maximus musculocutaneous flap in a rat model [15]. They found that besides the non-specific, acute phase-driven micro-rheological alterations, the I/R caused deterioration in flap microcirculation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Klarik et al examined the hemorheological (red blood cell deformability and aggregation) and microcirculatory parameters (laser Doppler fluxmetry) after two-hour ischemia in latissimus dorsicutaneus maximus musculocutaneous flap in a rat model [15]. They found that besides the non-specific, acute phase-driven micro-rheological alterations, the I/R caused deterioration in flap microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…Microcirculatory follow-up was important in prediction the possible postoperative complications, such as flap thrombosis and consequent flap failure [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this aspect the intra-or early postoperative monitoring has a great importance 1,3,20 . In previous animal models the method was found to be useful to reflect or even predict postoperative complications 4 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Viability of various composite flaps is a key factor of the successful reconstructive operation. Numerous clinical and experimental studies demonstrated that microcirculatory disturbance may lead to flap failure [1][2][3][4] . Mechanical damage during flap preparation and positioning, bending and torquation of pedicle's vessels, thrombosis, edema, inflammation, all may lead to complication, resulting in flap necrosis 5,6 .…”
Section: ■ Introductionmentioning
confidence: 99%